Massive Jurassic slab break-off revealed by a multidisciplinary reappraisal of the Chon Aike silicic large igneous province - Navarrete Granzotto, César Rodrigo (2024)
The origin of the Chon Aike silicic large igneous province (SLIP) is a matter of intense debate, with contrasting hypotheses that range from intraplate settings linked to mantle plume impingement to subduction-related protracted arc magmatism in an active margin. In this study, we propose a new model for the origin of this SLIP based on a multidisciplinary dataset from Patagonia, a comprehensive literature review of southwestern Gondwana, and the results of 2-D thermochemical modeling. We demonstrate that the partial melting of subducted rocks during a massive slab break-off and the subsequent piecemeal sinking of a previously flattened oceanic lithosphere beneath southwestern Gondwana best reconciles most of the data from this magmaticprovince. Geophysical, geochronological, geochemical, and isotopic data from Chon Aike SLIP, combined with the understanding of the tectonic regime, ore deposits, Jurassic geological events in southwestern Gondwana and numerical modeling results, support an origin primarily linked to the partial melting of partially eclogitized metabasaltic and metasedimentary rocks, enhanced by a warm ambient mantle associated with supercontinent thermal insulation and the thermal effects of the Karoo mantle plume impingement. The demise of the flat slab through large-scale slab break-off would have led to the partial melting of a mixture largely composed of these extensively underplated components and mantle batches. These melts would have variably interacted with mantle and continental rocks and melts, resulting in the formation of most of the Chon Aike SLIP. The reestablishment of the magmatic arc after the initial stages of slab break-off seems to have only affected the northwestern part of this SLIP.